Novel stereoselective addition of some nucleophiles to 2,3-bis(methylsulfanyl) norbornenobenzoquinone - Wladislaw, B.; DiVitta, C.; Marzorati, L.; Campos, IPD; Lucchini, V (Elsevier B.V., 1997)
2,3-Bis(methylsulfanyl)norbomenobenzoquinone undergoes reaction with nitrogen, oxygen, sulfur or carbon nucleophiles to give the trisubstituted adducts containing the new substituent at the ring junction. Their configurations are assigned by H-1 NMR spectroscopy and NOE enhancement experiments. (C) 1997 Elsevier B.V. Ltd.